RENEWAL OF CRIMINAL LAW: DRAFT OF INDONESIAN CRIMINAL CODE, SPIRIT OF CODIFICATION AND ITS EFFECTS ON LAW HARMONIZATION - Octora, Rachel (UI Scholars Hub, 2016)
Law-making process needs to be observed by public, and also by legal scholar, the purpose is to avoid inconsistency between new regulation and existing regulation. This paper will describe about Draft of Indonesian Criminal Code. Countries that use Civil Law System, especially in criminal law, principle of legality becomes the most important principle. Indonesia currently designing recodification of the Criminal Code and aspire to have their very own criminal codification. Draft of Indonesian Criminal Code is now still waiting to be enacted. It will potentially cause disharmony in the implementation process, because of the probability that one criminal act regulated by more than one regulation. Based on this research, Will reach the conclusions those criminal acts which have been regulated in another regulation outside the code, do not need to be re-regulated inside the code because it will potentially overlapping and confusing in the implementation process. If the Draft of Indonesian Criminal Code finally enacted, the way to harmonizing regulations inside and outside the code has to be based on transitional regulation inside the Code which states the applicable regulation is one that causing benefit for the offender.